2004
DOI: 10.1080/1369183042000200731
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between marriage, divorce and migration in a British data set

Abstract: Family and kinship factors are important as motivations for moving and as major considerations promoting or deferring migration. This is most obviously the case for family events that involve the establishment of new households or the dissolution of old ones, through cohabitation, marriage, separation and divorce. The overall importance of such events can be gauged from life-history data where the timing of residential moves and family events are both recorded. One such data set, from the Social Change and Eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 22 publications
1
57
0
Order By: Relevance
“…Using US data, Clark and Huang (2004) and Clark and Withers (2007) found a positive impact of union dissolution on long-distance moves. And for Britain, Flowerdew and Al-Hamad (2004) found that migration was elevated both immediately before and after union dissolution. Yet most of these findings, while they are few and far between and not in complete agreement, suggest that union dissolution tends to elevate propensities for all forms of spatial mobility, including long-distance migration -an observation that is consistent with one of Mincer's (1978: 769) untested hypotheses: " .…”
Section: Introductionmentioning
confidence: 99%
“…Using US data, Clark and Huang (2004) and Clark and Withers (2007) found a positive impact of union dissolution on long-distance moves. And for Britain, Flowerdew and Al-Hamad (2004) found that migration was elevated both immediately before and after union dissolution. Yet most of these findings, while they are few and far between and not in complete agreement, suggest that union dissolution tends to elevate propensities for all forms of spatial mobility, including long-distance migration -an observation that is consistent with one of Mincer's (1978: 769) untested hypotheses: " .…”
Section: Introductionmentioning
confidence: 99%
“…While demographic and socioeconomic characteristics are often included in mobility studies, life events -the active drivers of mobility -are often excluded. Studies examining life events such as union formation (Grundy and Fox 1985) and dissolution (Flowerdew and Al-Hamad 2004;van Ham 2007, 2010;Clark 2013), childbirth (Clark, Deurloo, and Dieleman 1994;Kulu 2005), and employment changes (Rabe and Taylor 2010) have determined that they exert an independent influence on increasing the likelihood of mobility over and above broad characteristics.…”
Section: Theoretical Limitations Within the Literaturementioning
confidence: 99%
“…Much spatial mobility is therefore reactive and consumption driven (Duncan and Newman 1976), with most moves made over short distances in order to minimise the disruption to the household (as workplaces, services and social contacts are still accessible from the new location) (Clark and Dieleman 1996). Housing needs and preferences which can produce housing stress can change as a result of events in the life course of household members, such as job losses (Böheim and Taylor 2002;Clark and Davies Withers 1999), or household formation and dissolution events (Feijten and van Ham 2010;Flowerdew and Al-Hamad 2004).…”
Section: Literature Reviewmentioning
confidence: 99%